THE IMPORTANCE PERFORMANCE MATRIX ANALYSIS (IPMA): SEBAGAI ALAT EVALUASI KEPUASAN DAN KEPENTINGAN PENGGUNA JALAN DI KOTA MANDIRI TANGERANG SELATAN - Resdiansyah Mansyur (Universitas Katolik Indonesia Atma Jaya, 2019)
The rapid growth of satelite city in South Tangerang will directly impact road infrastructure and environmental conditions. The purpose of this paper is to evaluate level of satisfaction and important of existing road infrastructure in satelite city. The study was to gain the perception of road users and other stakeholders regarding various elements of satelite city self-reliance in maintaining the quality of road infrastructure. Using one of satelite city in South Tangerang as a case, the specific research objectives are to: ascertain road user level of satisfaction with the road infrastructure and determine the most dominant factors affecting road user satisfaction. A questionnaire survey was conducted on road users in three selected roads at satelite city. Through a random sampling, a total of 384 responses were collected. After the survey, interviews were conducted with subject matter experts to understand the current practices and possible solutions to the problems. Data processing using SPSS software version 20.00 and analysed using Cronbach Alpha (α) statistical method and Importance Performance Matrix Analysis (IPMA) to know the level of satisfaction and important of user. The priority matrix analysis result shown that the safety improvement and comfort facilities for pedestrians, disabled provider and cyclists become important elements. The ranking of the importance elements in road performance based on user perceptions obtained the highest average value of 22 % which shows that the road safety element is the most important element in road performance.